Ratio Legis Of The Policy On The Formulation Of Electronic Evidence In Special Crime - Madinah Mokobombang; Achmad Ruslan; Syamsuddin Muchtar (LEGAL BRIEF, 2021)
This study aims to identify and analyze the existence of electronic evidence in Law No. 20 of 2001 concerning corruption and Law No. 8 of 2010 concerning the eradication of money laundering in terms of the ratio of legislators to the legislature. This research uses normative research methods, which focus on written studies, namely legislation, legal theory, legal principles, library documents, and can be in the form of scientific works of legal scholars (doctrine). These legal materials were analyzed using a statutory approach in order to obtain a systematic picture which was then studied further normatively using qualitative analysis techniques with data analysis methods linked to theories from literature studies so as to obtain answers to problems. The results of the study indicate that: In terms of the ratio of legislators to the legislature, the legislators (DPR) did not discuss the existence of the position of electronic evidence as an extension of the evidence of guidance in the corruption law and electronic evidence as evidence that stand alone in the money laundering law. the legislators only explained two reasons for recognizing electronic evidence, namely as a form of anticipation of the development of information technology and as an intensive effort to uncover criminal acts. For the same reason, without any specific reason underlying the difference in the existence of the electronic evidence, it shows that the form of recognition of the electronic evidence is an open policy for legislators, so that the existence of the position of electronic evidence can be changed based on strategic considerations in accelerating criminal disclosure process.